Формування творчих умінь у майбутніх інженерів-педагогів - Романовська, Олена Олександрівна (НТУ "ХПІ", 2013)
Статтю присвячено проблемі формування творчих умінь у майбутніх інженерів-педагогів під час їх професійної підготовки. Визначено суть поняття творчі уміння; визначено основні компоненти творчих умінь інженера-педагога; теоретично обґрунтовано методику формування творчих умінь майбутнього інженера-педагога, основний зміст якої полягає у впровадженні в начальний процес при вивченні дисципліни «Комунікативні процеси в педагогічній діяльності» методів, що стимулюють розвиток творчого мислення.

The article is devoted to the formation of creative skills of future engineers-teachers during their training. Defined the essence of the concept of creative skills, the basic components of the creative skills of the engineer-teacher; theoretically grounded method of formation of creative skills of the future engineer-teacher, the basic meaning of which is the implementation of the educational process in the study of the discipline "Communication processes in educational activities" methods that promote the development of creative thinking.
Formation of the creative skills of the future engineers-teachers
Keywords: підготовка професійна; підготовка кадрів; підготовка фахівців; процес навчальний; мислення творче; процеси комунікативні; creativity; creative skills